FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MENUNDA TUGAS AKADEMIK MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN FT UNP - 677-685 , Andika (CIVED, 2015)
Abstract This study stems from the students who often procrastinate in fulfilling the academic, this study is to reveal and analyze the factors that dominant influence on the behavior of delaying the academic tasks or also called academic procrastination in students of Technical Education Building FT UNP, this type of research is descriptive and factor analysis. Descriptive analysis known that internal factors are the most dominant influence on student academic procrastination Study Program Building Techniques FT UNP is not like task with a large degree achievement of 56.377 % and external factors the most dominant influence is the environment with a large degree achievement of 70.051 %. As for the results obtained by factor analysis four factors formed and was named among other personality factors, factors laziness, self decision factors and factors initiative. Keywords: mempengaruhi, prokrastinasi akademik